Engine driven feed chopper technology demonstration for animals' feed preparation in the selected districts of AGP-II in Harari region and Dire Dawa Administration - Abdulaziz Teha Umer; Ibsa Aliyi Usmane; Jamal Nur; Abdulahi Umer (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2020)
Animal feed preparation in very quality and good enough quantity way in short period time helps small holder famers to feed their livestock in good manner. To make this animal feed preparation demonstrating Feed Chopper Machine which is hay cutting machine that use for uniform chopping of fodder for livestock's' feed is good option. Thus, demonstration of feed chopper was undertaken with objectives of demonstrate and evaluate engine driven feed chopper technology, create awareness among farmers, developmental agents, subject matter specialists and other participant stakeholders on engine driven feed chopper technology and build farmers' knowledge and skill of production and management of the enterprises. A total of 80 trial farmers were selected from Sofi and Wahil potential sorghum and maize growing kebeles and training was given for participants on how to use the machine for livestock feed forage chopping. The machine could chop time of chopping 0.03hr, chopping efficiency 95%, Wt of off cut length 19 to 31.54 %. Output capacity 88.24 kg/h, and also the machine ensure safety of feed, provide good fodder for animal, save work time, and get protection of feed from dust and make the feed easily palatable. And there was statistically significance difference of parameters related with stalk that is moisture content at p<5%, output capacity, chopping efficiency and chopping rate at p<1%. Therefore, it is better to work on the multiplication and promotion of this engine driven feed chopper technology by government, Non-government and other stakeholders to small holder farmers in the study areas and other places.